Pertumbuhan dan Perkembangan Sosial Peserta Didik di Sekolah - Nur Alifah, Siti (Mulya Literasi Publishing, 2025)
The social growth and development of students are critical aspects of their overall development. Social development involves acquiring skills, behaviours, and attitudes that enable students to interact effectively with others and integrate into society. This process is influenced by factors such as family, peers, school environment, and cultural background. Understanding social growth helps educators and parents foster positive social behaviours, emotional intelligence, and interpersonal relationships in students. By promoting inclusivity, collaboration, and empathy, students can develop a strong foundation for navigating social interactions and contributing positively to their communities.